Analgesic efficacy of lidocaine and multimodal analgesia for chest tube removal: A randomized trial study - Valdecy Ferreira de Oliveira Pinheiro; José Madson Vidal da Costa; Marcelo Matos Cascudo; Ênio de Oliveira Pinheiro; Maria Angela Ferreira Fernandes; Ivonete Batista de Araujo (Universidade de São Paulo, 2015)
Objective: to assess the analgesic efficacy of subcutaneous lidocaine and multimodal analgesia for chest tube removal following heart surgery. Methods: sixty volunteers were randomly allocated in two groups; 30 participants in the experimental group were given 1% subcutaneous lidocaine, and 30 controls were given a multimodal analgesia regime comprising systemic anti-inflammatory agents and opioids. The intensity and quality of pain and trait and state anxiety were assessed. The association between independent variables and final outcome was assessed by means of the Chi-squared test with Yates' correction and Fisher's exact test. Results: the groups did not exhibit significant difference with respect to the intensity of pain upon chest tube removal (p= 0.47). The most frequent descriptors of pain reported by the participants were pressing, sharp, pricking, burning and unbearable. Conclusion: the present study suggests that the analgesic effect of the subcutaneous administration of 1% lidocaine combined with multimodal analgesia is most efficacious.